Peran Komite Sekolah Sebagai Advisory Agency dalam Meningkatkan Mutu Pendidikan di MAN 2 Flores Timur: The Role of the School Committee as an Advisory Agency in Improving the Quality of Education at MAN 2 East Flores - Fazlur Rahman RM; Hikmah Hariyati (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
Community involvement or participation is one form of effort to improve the quality of education, as stated in Law 25 of 2000, which calls for increased family and community participation in the implementation of education. These efforts include the government forming a school committee. The method used is a descriptive qualitative method, with data collected through observation, interviews, and document analysis (1). The subjects of this study included the principal, teachers, school committee members, and parents' representatives. The urgency of implementing the school committee's work at MAN 2 East Flores in supporting the development and improvement of the quality of education has not been running optimally. The school committee should play an active role in formulating and overseeing strategic policies that can strengthen the educational process in madrasas. However, in reality, this role has not been implemented optimally. One aspect that has not been seen strongly is balanced cooperation and communication between the school committee and the madrasah. The involvement and contribution of the school committee as an advisory agency is quite good, especially in three aspects, namely 1) Providing Considerations on School Policies, 2) Recommending Program Preparation, the school committee in its role has also carried out one of several other functions as an advisory agency well and 3) Providing Advice in Fund Management, in the aspect of budget or fund management, the school committee is also committed to continuing to provide input so that in the process of managing the budget or funds until their use must be on target and in accordance with what was agreed upon and of course in its use must support the improvement of the quality of education.